Culturally Sustaining Pedagogy through Banyuwangi Artsin Elementary Education - Martadi, Martadi; Sampurno, Muchammad Bayu Tejo (Universitas Negeri Semarang, 2025)
This study presents the design and development of a culturally sustaining pedagogical model in elementary education by integrating Banyuwangi’s traditional arts into a thematic learning framework. Using a Design-Based Research (DBR) methodology, this study systematically develops, tests, and refines an instructional model incorporating traditional arts such as the Gandrung and Barong dances and culturally resonant learning media like puzzles, multimedia, and puppets. This approach emphasizes character development alongside academic learning, fostering values such as empathy, respect, and cultural identity. The model incorporates culturally resonant media—including puzzles, multimedia, and puppets—featuring iconic local characters, Tole and Jebeng, to engage students and connect lessons to their cultural heritage. Observational data from classroom applications reveal enhanced student motivation, social identity, and moral reasoning. Teachers and educational experts rated the model highly for its feasibility, relevance, and impact on character and cognitive development. Despite challenges such as the need for specialized teacher training and scalability across diverse cultural contexts, the findings underscore the transformative potential of integrating local arts into educational curricula. This research contributes to the discourse on culturally responsive education by providing a replicable framework that aligns academic rigor with the preservation of cultural heritage, equipping students with essential values for navigating a globalized world. Future work is recommended to evaluate long-term impacts and adaptations for broader cultural settings.